Spirit of a nation the story of Australia's Christian heritage - Piggin, Stuart (Sydney, NSW Strand, 2004)
Inlcudes bibliographical references and index.
First edition published as : Evangelical Christianity in Australia : spirit, word and world. 1996. Which see also.
Keywords: Church history -- Australia -- modern times; Evangelicalism -- Australia